2011
DOI: 10.1007/s10722-011-9742-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and relationships of multipurpose seabuckthorn (Hippophae L.) germplasm from the Indian Himalayas as assessed by AFLP and SAMPL markers

Abstract: IMPF: 01.55Seabuckthorn, a non-leguminous nodule bearing dioecious shrub, is a storehouse of neutraceutical, pharmaceutical and cosmetic usage. The 348 genotypes of Hippophae rhamnoides ssp. turkestanica, H. salicifolia and H. tibetana were collected from 194 locations at 46 major sites across 1,500km from north-east to north-west Himalayas, harboring one of the most harsh, highly variable climatic and ecological conditions and rugged rocky terrain in the range of 3,000?5,000 metres altitude. Amplified fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
1
19
1
1
Order By: Relevance
“…On the other hand, Azizi et al(2009) visualized 558 scorable bands by using 7 SAMPL primer combinations, where the percentage of polymorphism across the oregano accessions ranged from 85% to 97% with an average of 92%. While, Raina et al(2012) and Biswas et al (2011) reported that the average number of bands per primer combination was 33 and 22.43, respectively.…”
Section: Polymorphism Among the Olive Varieties As Detected By The DImentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Azizi et al(2009) visualized 558 scorable bands by using 7 SAMPL primer combinations, where the percentage of polymorphism across the oregano accessions ranged from 85% to 97% with an average of 92%. While, Raina et al(2012) and Biswas et al (2011) reported that the average number of bands per primer combination was 33 and 22.43, respectively.…”
Section: Polymorphism Among the Olive Varieties As Detected By The DImentioning
confidence: 99%
“…Therefore, it is more applicable when low level of diversity is expected (Sarwat et al, 2008). SAMPL helped unravel genetic diversity in wheat (Roy et al, 2004), grapevine (Cretazzo et al, 2010), citrus (Biswas et al, 2011), walnut (Kafkas et al, 2005), seabuckthorn (Raina et al, 2012). Given that, it was used to generate SCAR markers in olives (Busconi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…H. rhamnoides has also an extremely wide distribution throughout the Indian Himalayas (Zeb 2004), where it grows naturally between 3000-5000 m a.s.l. (Raina et al 2012).…”
Section: Distribution Rangementioning
confidence: 99%
“…There are four Hippophae species namely, H. rhamnoides, H. salicifolia, H. tibetana, and H. gyantsensis that represent the genus in India (Naithani 2004). Ladakh hosts H. rhamnoides and H. salicifolia (Ali and Kaul 2011) whereas H. salicifolia has been reported in Sikkim and Arunachal Pradesh of North East India (Naithani 2004;Raina et al 2012). Plant of Hippophae species are dioecious with separate male and female characteristics.…”
Section: Introductionmentioning
confidence: 99%